2016
DOI: 10.1556/1886.2016.00030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Toxoplasma gondii infection on symptoms and signs of premenstrual syndrome: A cross-sectional study

Abstract: Infection with Toxoplasma gondii in brain may cause some symptoms that resemble those in women with premenstrual syndrome. To determine the association of T. gondii infection with symptoms and signs of premenstrual syndrome, we examined 489 women aged 30–40 years old. Sera of participants were analyzed for the presence of anti-Toxoplasma IgG and IgM antibodies using enzyme-linked immunoassays (EIA) and T. gondii DNA by polymerase chain reaction (PCR).Anti-T. gondii IgG antibodies were found in 38 (7.8%) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This initial immune response is mediated by cytokines and chemokines released by invaded enterocytes and by lymphocytes and macrophages which migrate to the mucosa 10‐12 . Diarrhea is common in some species infected with T gondii as chicken, 13 pigs, 14 and immunodepressed humans 15‐18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This initial immune response is mediated by cytokines and chemokines released by invaded enterocytes and by lymphocytes and macrophages which migrate to the mucosa 10‐12 . Diarrhea is common in some species infected with T gondii as chicken, 13 pigs, 14 and immunodepressed humans 15‐18 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Diarrhea is common in some species infected with T gondii as chicken, 13 pigs, 14 and immunodepressed humans. [15][16][17][18] Diarrhea is a clinical sign that can indicate disturbance of the enteric nervous system. 19 Alterations in the frequency and intensity of the intestinal contractions are observed during the diarrhea triggered by several pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, T. gondii causes pathology in liver, pancreas, spleen, and mesenteric lymph nodes in several animal species [ 18–20 ]. Furthermore, T. gondii infection was associated with abdominal inflammation in women [ 27 ]. Interestingly, in the current study, stratification by gender showed an association between T. gondii infection and frequent abdominal pain in women.…”
Section: Discussionmentioning
confidence: 99%
“…Most T. gondii infections are asymptomatic; people developing parasitic toxoplasmosis show no signs of infection if they have an intact immune system 4 . However, clinical manifestations of the disease called toxoplasmosis can be seen in some individuals 5 . Toxoplasmosis may involve lymph nodes, eyes, or the central nervous system 6 .…”
Section: Introductionmentioning
confidence: 99%
“… 4 However, clinical manifestations of the disease called toxoplasmosis can be seen in some individuals. 5 Toxoplasmosis may involve lymph nodes, eyes, or the central nervous system. 6 Toxoplasmosis can be life‐threatening in immunocompromised patients.…”
Section: Introductionmentioning
confidence: 99%